2020
DOI: 10.1002/mrd.23400
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A‐induced mechanistic impairment of decidualization

Abstract: Decidualization is a crucial precedent to embryo implantation, as its impairment is a major contributor to female infertility and pregnancy complications. Unraveling the molecular mechanisms involved in the impairment of decidualization has been a subject of interest in the field of reproductive medicine. Evidence from several experimental settings show that exposure to bisphenol A (BPA), an endocrine‐disrupting chemical, affects the expression of several molecules that are involved in decidualization. Both lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…However, a prevailing concern regarding BPA exposure is its ability to bind to the estrogen receptors α (ERα) and β (ERβ), through which this endocrine-active substance may affect humans at doses below the presumably safe tolerable daily intake. Several studies have suggested an adverse endocrine disruptive effect by BPA at doses as low as 0.025-0.200 µg/kg/day, such as a decrease in daily sperm production and fertility in males at a dose of 0.2 µg/kg/day [13] stimulation of mammary gland development at 0.025-0.250 µg/kg/day [14,16] and a decrease in antioxidant enzymes at 0.2 µg/kg/day [17]. In addition to these multi-system health effects being linked to BPA, there is evidence of transcription of proliferation and differentiation-related genes in response to low-dose BPA in activated ERβ in oral keratinocytes, which are the first targets of BPA by oral intake [18] showed a sublingual absorption of BPA besides typical digestion, which shows that BPA can diffuse through oral mucosal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, a prevailing concern regarding BPA exposure is its ability to bind to the estrogen receptors α (ERα) and β (ERβ), through which this endocrine-active substance may affect humans at doses below the presumably safe tolerable daily intake. Several studies have suggested an adverse endocrine disruptive effect by BPA at doses as low as 0.025-0.200 µg/kg/day, such as a decrease in daily sperm production and fertility in males at a dose of 0.2 µg/kg/day [13] stimulation of mammary gland development at 0.025-0.250 µg/kg/day [14,16] and a decrease in antioxidant enzymes at 0.2 µg/kg/day [17]. In addition to these multi-system health effects being linked to BPA, there is evidence of transcription of proliferation and differentiation-related genes in response to low-dose BPA in activated ERβ in oral keratinocytes, which are the first targets of BPA by oral intake [18] showed a sublingual absorption of BPA besides typical digestion, which shows that BPA can diffuse through oral mucosal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, after intervention with bisphenol A, the expression of epithelial sodium channel alpha (ENaCα) protein in the decidua was significantly down-regulated detected by immunohistochemistry [ 142 ]. Thus, it has been suggested that exposure to BPA leads to impaired decidualization through a reduced serum glucocorticoid-induced kinase 1-mediated downregulation of ENACα [ 142 , 150 ]. In epidemiological studies, polychlorinated biphenyls (PCB) and other chlorides have been linked with serious adverse effects on maternal health and fetal development including growth restriction [ 151 ] impaired immune response [ 152 ] and neurobehavioral deficits [ 153 ] in the child.…”
Section: The Effect Of Chemical Exposure On Placental Ion Channelsmentioning
confidence: 99%
“…BPA has been detected in most of the human body fluids including serum ( Takeuchi & Tsutsumi, 2002 ), urine ( Calafat et al, 2008 ), breast milk ( Ye et al, 2006 ), amniotic fluids ( Yamada et al, 2002 ), ovarian follicular fluid ( Ikezuki et al, 2002 ), and umbilical cord blood ( Kuroda et al, 2003 ). Increasing evidence of cause-and-effect relationship between BPA exposure and female reproductive disorders have been obtained from animal experiments as well as cell culture-based in vitro studies ( Palioura & Diamanti-Kandarakis, 2015 ; Bloom et al, 2016 ; Ziv-Gal & Flaw, 2016 ; Nelson et al, 2020 ; Pivonello et al, 2020 ). However, the precise biochemical and molecular mechanism(s) by which BPA interferes with steroidogenesis in the ovarian cells still remain unclear.…”
Section: Introductionmentioning
confidence: 99%